CHARACTERIZATION OF HYBRID-FORMAMIDINIUM BISMUTH BROMIDE PEROVSKITE MATERIAL (FABi2Br9) SYNTHESIZED VIA GROWTH ASSISTED TECHNIQUE FOR SOLAR CELLS APPLICATION - Salisu, Bashir (FUDMA JOURNAL OF SCIENCES, 2021)
ABSTRACT In the last decade, organic-inorganic perovskite solar cells (PSCs) have had tremendous success, raising their power conversion efficiency from 3.8% in 2009(T, A, K, & Y, 2009) to >25.6% (Li et al., 2021). Perovskite material is newly emergent, third-generation solar cells, it generally refers to any composite that has structure like that of calcium titanium oxide (CaTiO2). It has a general formula ABXÂ3, where A refers to an organic compound, B is an inorganic and X represents the halides. In this research, a Hybrid-Formamidinium Bismuth Bromide Perovskite solar cell (FABi2Br9) was synthesized via a novel crystal growth process and subjected to characterization for determining its optoelectronic properties for solar cells application. The x-ray diffraction (XDR) results revealed the crystal hexagonal structure of FABi2Br9, the crystal sizes were obtained and it gives an excellent size (74nm) for light absorption material. The bandgap was determined using ultraviolet-visible spectroscopy (U.V vis) which was found to be 1.80eV which is within the required range for an absorbing layer in a solar cell architecture. Nuclear magnetic resonance (NMR) and was used to identify the organic content purity of the composite. In conclusion, FABi2Br9 was found to be pure with excellent optoelectronics properties that can readily be used as an absorbent layer in perovskite solar cells architecture